3D Printed Mini-Floating-Polypill for Parkinson's Disease: Combination of Levodopa, Benserazide, and Pramipexole in Various Dosing for Personalized Therapy - Hellen Windolf; Rebecca Chamberlain; Jörg Breitkreutz; Julian Quodbach (MDPI AG, 2022)
Therapy for Parkinson's disease is quite challenging. Numerous drugs are available for symptomatic treatment, and levodopa (LD), in combination with a dopa decarboxylase inhibitor (e.g., benserazide (BZ)), has been the drug of choice for years. As the disease progresses, therapy must be supplemented with a dopamine agonist (e.g., pramipexole (PDM)). Side effects increase, as do the required dose and dosing intervals. For these specific requirements of drug therapy, the 3D printing method fused deposition modelling (FDM) was applied in this study for personalized therapy. Hot melt extrusion was utilized to produce two different compositions into filaments: PDM and polyvinyl alcohol for rapid drug release and a fixed combination of LD/BZ (4:1) in an ethylene-vinyl acetate copolymer matrix for prolonged drug release. Since LD is absorbed in the upper gastrointestinal tract, a formulation that floats in gastric fluid was desired to prolong API absorption. Using the FDM 3D printing process, different polypill geometries were printed from both filaments, with variable dosages. Dosage forms with 15-180 mg LD could be printed, showing similar release rates (f2 > 50). In addition, a mini drug delivery dosage form was printed that released 75% LD/BZ within 750 min and could be used as a gastric retentive drug delivery system due to the floating properties of the composition. The floating mini-polypill was designed to accommodate patients' swallowing difficulties and to allow for individualized dosing with an API release over a longer period of time.